Study on the Quality of Broiler Carcasses Stored at Room Temperature After Steaming Treatments - Hantoro, A; Rahardjo, Djoko; Santoso, BS (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2005)
This research is conducted to study the effect of steaming time before marketing on quality and storage time of broiler carcasses. A Completely Randomized Design (CRD) with factorial 3 x 4 was used. The first factor was steaming time, i.e. steaming at 80ËC for 2 minutes, 4 minutes, and 6 minutes. The second factor was storage time at room temperature, i.e. initial condition, 4, 8, and 12 hours. The parameters observed were pH, water holding capacity, and total number of bacteria. Results showed that the interaction between steaming time and storage time had significant effect on pH, andÂ total number of bacteria. Storage time had significant effect on water holding capacity of broiler carcasses. It can be concluded that steaming at 80ËC before marketing significantly decreases total number of bacteria. Meanwhile, broiler carcasses stored for 8 hour at room temperature showed no significant decrease of carcass quality (pH, water holding capacity and total number of bacteria). (Animal Production 7(1): 1-5 (2005)Â Key words: Quality of broiler carcasses, steaming time, storage time, room temperature